Long-Lasting Impairments in Quadriceps Mitochondrial Health, Muscle Size, and Phenotypic Composition Are Present After Non-invasive Anterior Cruciate Ligament Injury - Davi, Steven M.; Ahn, Ahram; White, McKenzie S.; Butterfield, Timothy A.; Kosmac, Kate; Kwon, Oh Sung; Lepley, Lindsey K. (Frontiers in Physiology, 2022)
Introduction: Despite rigorous rehabilitation aimed at restoring muscle health, anterior cruciate ligament (ACL) injury is often hallmarked by significant long-term quadriceps muscle weakness. Derangements in mitochondrial function are a common feature of various atrophying conditions, yet it is unclear to what extent mitochondria are involved in the detrimental sequela of quadriceps dysfunction after ACL injury. Using a preclinical, non-invasive ACL injury rodent model, our objective was to explore the direct effect of an isolated ACL injury on mitochondrial function, muscle atrophy, and muscle phenotypic transitions. Methods: A total of 40 male and female, Long Evans rats (16-week-old) were exposed to non-invasive ACL injury, while 8 additional rats served as controls. Rats were euthanized at 3, 7, 14, 28, and 56 days after ACL injury, and vastus lateralis muscles were extracted to measure the mitochondrial respiratory control ratio (RCR; state 3 respiration / state 4 respiration), mitochondrial reaction oxygen species (ROS) production, fiber cross sectional area (CSA), and fiber phenotyping. Alterations in mitochondrial function and ROS production were detected using two-way (sex:group) analyses of variance. To determine if mitochondrial characteristics were related to fiber atrophy, individual linear mixed effect models were run by sex. Results: Mitochondria-derived ROS increased from days 7-56 after ACL injury (30-100%, P<0.05), concomitant with a 2-fold reduction in RCR (P<0.05). Post-injury, male rats displayed decreases in fiber CSA (days 7,14,56; P < 0.05), loss of IIa fibers (day 7; P < 0.05), and an increase in IIb fibers (day 7; P < 0.05), while females displayed no changes in CSA or phenotyping (P>0.05). Males displayed a positive relationship between state 3 respiration and CSA at days 14 and 56 (P <0.05), while females only displayed a similar trend at day 14 (P = 0.05). Conclusions: Long-lasting impairments in quadriceps mitochondrial health are present after ACL injury and play a key role in the dysregulation of quadriceps muscle size and composition. Our preclinical data indicate that using mitoprotective therapies may be a potential therapeutic strategy to mitigate alterations in muscle size and characteristic after ACL injury.